2017
DOI: 10.1016/j.combustflame.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The high charge fraction of flame-generated particles in the size range below 3 nm measured by enhanced particle detectors

Abstract: Charging in flames significantly affects the properties of the resultant particles produced because of its influence in almost all stages of particle formation. The charging characteristics of flamegenerated sub-3 nm particles were investigated with three enhanced particle detectors including a high resolution differential mobility analyzer (DMA) coupled with an electrometer, a particle size magnifier coupled with a butanol-based condensation particle counter (PSM-bCPC), and an atmospheric pressure interface t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…Approximate mass values of 140 amu and 70 amu for positive and negative ions were used, which are in the range of existing measurement results obtained with mass spectrometers (Fialkov 1997). These atomic mass values also agree with a recent study on the measurement of premixed flat flame-generated ions with an atmospheric pressure-inlet time-of-flight mass spectrometer, where the dominant positive charge carriers were hydrocarbons (100-250 amu) and dominant negative charge carriers were nitrate-related ions (62 amu and 125 amu; Wang et al 2017a). As pointed out by the study of the sensitivity analysis in Fuchs' charging model, the main influential variable is the difference between the positive and negative ion mobilities, which were measured accurately in this study (Tigges et al 2015).…”
Section: Simulation Methodssupporting
confidence: 86%
See 1 more Smart Citation
“…Approximate mass values of 140 amu and 70 amu for positive and negative ions were used, which are in the range of existing measurement results obtained with mass spectrometers (Fialkov 1997). These atomic mass values also agree with a recent study on the measurement of premixed flat flame-generated ions with an atmospheric pressure-inlet time-of-flight mass spectrometer, where the dominant positive charge carriers were hydrocarbons (100-250 amu) and dominant negative charge carriers were nitrate-related ions (62 amu and 125 amu; Wang et al 2017a). As pointed out by the study of the sensitivity analysis in Fuchs' charging model, the main influential variable is the difference between the positive and negative ion mobilities, which were measured accurately in this study (Tigges et al 2015).…”
Section: Simulation Methodssupporting
confidence: 86%
“…At the same time, because of chemical ionization and thermal ionization mechanisms (Fialkov 1997), flames generate large numbers of ions and charged clusters with concentrations as high as 10 10 /cm 3 . A recent study conducted with a series of enhanced particle detectors showed that the fraction of charged species can be high in a premixed flame (Wang et al 2017a). The presence of these ions makes the flame a quasi-neutral plasma that may notably affect the property of the produced particles.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the real CPCs, an ideal CPC with d50 at 1.5 nm is included as a reference in the analysis to distinguish between the uncertainties related to the CPC d50 curve and other factors. Figure 1 upper panel presents the d50 curves of the three CPCs, which are published in Kangasluoma et al (2017) for the vWCPC and 3777 and in Vanhanen et al (2011) for the A11. The fits to the curves are according to the following equation:…”
Section: Methods 21 Instrumentation Used In the Numerical Simulationsmentioning
confidence: 99%
“…The purpose of this study is to numerically investigate the uncertainties related to the particle counting with three different size distributions and four CPCs in five different case studies. The main focus is placed upon the challenges arising from narrow input particle number size distributions, when they are sampled with a theoretical CPC parametrized based on Kangasluoma et al (2017) and Vanhanen et al (2011). The CPC counting statistics related uncertainty is first studied in a general CPC counting experiment, and then examined based on a published state-of-the-art instrument utilizing the DMA-CPC technique.…”
mentioning
confidence: 99%
“…If the composition of the sampled particles is completely unknown, the obtained particle concentrations at the size range of the d50 can have significant uncertainties. The effect of particle charge on the d50 was shown to be up to approximately 0.5 nm, which has implications for system characterizations where the fraction of charged particles can be expected to be high (Wang et al, 2017), or CPC calibration is conducted with charged particles, sampled particles are neutral and high precision d50 is required.…”
Section: Discussionmentioning
confidence: 99%